Validation of NIR Model for On-line Monitoring of Flos Lonicera Japonica Extraction Process with Different Batches of Materials - Sui, Chenglin; Wu, Zhisheng; Peng, Yanfang; Zou, Luwei; Pei, Yanling; Shi, Xinyuan; Qiao, Yanjiang (International Journal of Online and Biomedical Engineering (iJOE), 2013)
In this study, on-line NIRs (Near Infrared Spectroscopy) monitoring technology, as a useful tool, has been verified during the extraction process of Flos Lonicera Japonica. To gain representative samples and accurate model result, the detrimental effects from NIR collecting circumstance were significantly reduced with meticulous designs. Based on what, different batches of Flos Lonicera Japonica material were real-time monitored in the extraction process. 10 design schemes were used to verify whether or not different batches could disturb predictive results of the quantitative model. According to a series of chemometric indicators, such as SEC, SECV, SEP, RPD, it is concluded that PLS models established by samples of different batches of raw herbs from the same source could be used to monitor the extraction process with acceptable accuracy. Our research has demonstrated that on-line NIRs monitoring technology as a fast, non-destructive and real-time monitoring tool could be utilized in traditional Chinese medicine preparation.